The Effects of Side-Casings Balance on Open-Deck-Ro-Ro Vessels in Term of Intact Stability. Issue 1 (August 2020) - Hasanudin,; Zubaydi, A; Aryawan, W D; Utama, I K A P
Abstract: Roll-on Roll-of (Ro-Ro) is one of the most favourite types of ship, which can carry passengers, cars, and cargoes at the same time. Reports from National Committee for Safety Transportation (KNKT) indicated that there is tendency of increase of Ro-Ro vessels accidents due to stability problems. The current paper discusses an Open-Car-Deck-Ro-Ro 40 m length without side-casings which capsized on Halmahera sea. The Ro-Ro was originally designed with side-casings on the right and left sides of car deck but removed to improve car deck capacity. The side-casings reduce one truck capacity, improve 72.539 GT, and improve survival stability. The Ro-Ro stability was calculated with four loading conditions with assumption weight and center gravity (KG) of the ship with and without side-casings the same. It shows all condition with added side-casings will increase righting lever GZ at angle ≥ 10°. Also, range righting lever curve GZ positive increase, at full load arrival 0°-29° become 0°-53°, at full load departure 0°-25° become 0°-42°, at ballast load arrival 0°-44° become 0°-66°, and at ballast load departure 0°-36° become 0°-52°. Then stability curves were assessed by Intact Stability Code 2008 (ISC 2008) obtained all load case ship with side-casings pass all criteria otherwise ship without side-casings fail especially area 30°-40° ≥ 0.03 m.rad and maximum GZ ≥ 25°. The case study indicates installed side-casings reduce cargo capacity but improve survival stability.